Struktur Kasta dan Penindasan Perempuan: Analisis Teologi Kontekstual Feminis dalam Budaya Ngada - Siprianus Soleman Senda; Yohanes Goa; Yohanes Baptista Virani Wogo; Fladimir Sie (STIPAS Keuskupan Agung Kupang, 2026)
The caste structure in the culture of Ngada Regency is an integral part of social identity that regulates the relationships, roles, and status of individuals within the community. However, in practice, this structure often has implications for gender inequality, especially for women, who experience marginalization in social, cultural, and symbolic spaces. The main problem of this research is how the caste structure contributes to the oppression of women and how feminist contextual theology can provide a framework for critical reflection on this reality. This research uses a qualitative method with a feminist contextual theological reflection approach, through literature analysis, socio-cultural studies, and theological hermeneutics on women's experiences as locus theologicus. The results show that the caste structure functions not only as a social identity system but also as a power structure that perpetuates gender injustice. From the perspective of feminist contextual theology, the experiences of oppressed women become a source of theological reflection that reveals the call to liberate and restore human dignity as the imago Dei. Thus, feminist contextual theology offers a critical and transformative framework for the Church and society to reflect on, critique, and transform unjust cultural structures towards more equal and humane relationships.